Psychological and Pedagogical Measures of Preventing Conflicts of Interest Among Employees of Law Enforcement Agencies - Serdyuk N.V; Naumov Y.G; Grishchenko D.N (Moscow State University of Psychology and Education, 2017)
The article considers significant characteristics of the phenomenon of corruption resistance of employees of internal affairs agencies as civil servants. The outlined problem of preventing corruption manifestations and conflicts of interests in operational and service activities is characterized by the fact that it exceeds the limits of legal regulation. The possible solution in this case might be the selection of relevant psychological and pedagogical measures of preventing the conflict of interests and the formation of corruption resistance in the personnel of the internal affairs bodies. The article describes the value basis of law enforcement service and personal meanings in the profession.